Development and challenges of direct-to-handset satellite communication - LI Sidong; LI Xiayu; SUN Jiancheng; KANG Shaoli; LIAO Yunfa; CHEN Junyan (Dianxin kexue)
In recent years, satellite Internet has developed rapidly, with major countries around the world actively promoting the construction of satellite Internet. The integration of satellite and terrestrial networks has become an important trend in the evolution towards 6G, and direct-to-handset satellite services has also become a selling point for terminal manufacturers. The current state of global direct-to-handset satellite services was summarized, three development routes for direct-to-handset satellite technology were proposed, and the challenges faced by direct-to-handset satellite connections were analyzed, including the integration of terminal chips, integration of satellite and terrestrial networks, and sharing of frequencies between satellite and terrestrial systems. The key technologies that need to be mastered for direct-to-handset satellite services were also outlined, such as time-frequency synchronization technology, random access technology, HARQ retransmission technology, and mobility management technology, and the future trends of direct-to-handset satellite services were assessed.